Robust H∞ Control of STMDs Used in Structural Systems by Hardware in the Loop Simulation Method - Aggumus, Huseyin; Guclu, Rahmi (MDPI, 2020)
This paper investigated the performance of a semi-active tuned mass damper (STMD) on a multi-degree of freedom (MDOF) building model. A magnetorheological (MR) damper was used as a control element that provided semi-activity in the STMD. The Hardware in the Loop Simulation (HILS) method was applied to mitigate the difficulty and expense of experimental studies, as well as to obtain more realistic results from numerical simulations. In the implementation of this method for the STMD, the MR damper was set up experimentally, other parts of the system were modeled as computer simulations, and studies were carried out by operating these two parts simultaneously. System performance was investigated by excitation with two different acceleration inputs produced from the natural frequencies of the MDOF building. Additionally, a robust H-infinity controller was designed to determine the voltage transmitted to the MR damper. The results showed that the HILS method could be applied successfully to STMDs used in structural systems, and robust H-infinity controls improve system responses with semi-active control applications. Moreover, the control performance of the MR damper develops with an increase in the mass of the STMD.
Keywords: structural control; semi-active mass damper (STMD); MR damper; robust H-infinity control; Hardware in the Loop Simulation (HILS); SEMIACTIVE CONTROL; VIBRATION CONTROL; BUILDINGS; ABSORBER; MODEL; ATMD; Engineering; Instruments & Instrumentation